Sense-making in crises: Diaries as window on experiences of vulnerability across the lifecourse - (:unkn) unknown (My University, 2025)
Major societal crises create ruptures in the lifecourse that have a variable impact depending on the resources, actions and context of the individual. Adopting a dynamic understanding of vulnerability, we propose a fine-grained analysis of how people experience and navigate ruptures. We use a sociocultural psychology approach that can contribute to the study of vulnerability the lifecourse in two ways. First, we will invigorate theorization with an analysis of sense-making in people’s experience of vulnerability. Second, we propose a methodological innovation by a cutting-edge combination of qualitative and quantitative analysis of longitudinal diaries in public repositories.
Keywords: life-course; diaries